Design of Web-Based Office Inventory Application at PT. Persepsi Karya Cipta - Sri Ratu Dewi; Muhamad Riyan Maulana (PT. Altaf Publishing Corp, 2024)
The management of inventory of goods at PT. Persepsi Karya Cipta is currently still ongoing. done with method manual by utilizing a recording system that is sometimes ineffective and inefficient. The difficulty of coordination between departments also makes inventory management more complicated. Therefore, the purpose from study This is to design and implement a web-based goods inventory application at PT. Persepsi Karya Cipta. The development method chosen is the waterfall method, which involves several stages such as needs analysis, system design, implementation, testing, and maintenance. At the analysis stage, information is searched for the system to be developed and inventory data is collected. The system design stage includes data structures, software architecture, and program views. Implementation involves translating the design into a programming language and creating a database. Application This web- based application has features such as user login, Home menu with a graph of the number of items per year, a menu to view items, rooms, item conditions, and user data. Testing was carried out using the Black box Testing method to ensure that it is in accordance with functional specifications. The results show that this application can facilitate inventory management, increase productivity, and facilitate coordination between departments. The result is a web-based office goods inventory application that has been successfully implemented at PT. Persepsi Karya Cipta, contributing to facilitating the recording, review, and data collection of office goods.